Money and inflation in the euro area during the financial crisis - Christian Dreger; Jürgen Wolters (European University Viadrina, Department of Business Administration and Economics, 2011)
This paper explores the stability of the relation between money demand for M3 and inflation in the euro area by including the recent period of the financial crisis. Evidence is based on a cointegration analysis, where inflation and asset prices are allowed to enter the long run relationship. By restricting the cointegrating space, equations for money and inflation are identified. The results indicate that the equilibrium evolution of M3 is still in line with money demand. In the long run, inflation is affected by asset prices and detrended output. Excess liquidity plays an important role for inflation dynamics. While the hypothesis of weak exogeneity is rejected for real money balances and inflation, real income, real asset prices and the term structure do not respond to deviations from the long run equilibria. A single equation analysis derived from this system still provides reliable information for the conduct of monetary policy in real time, since the error correction terms are very similar to those obtained by the system approach. To monitor the monetary development, a single money demand equation is sufficient, at least as a rough indication.
Keywords: C22; C52; E41; 330; Money demand; inflation; excess liquidity; cointegration analysis; Geldnachfrage; Inflation; Gesamtwirtschaftliche Liquidität; Kointegration; Schätzung; Finanzmarktkrise; EU-Staaten